Preparation of Zeolite Y using local raw material rice husk as a silica source - Rahman, Md. Mokhlesur; N, Hasnida; Wan Nik, Wan Mohd Norsani (International Network for the Availability of Scientific Publications, 2009)
The locally available rice husk is found to provide a good alternative source of highly active silica for the synthesis of zeolites. The present synthesis of zeolite Y using seed and feed gel method yields maximum crystallinity and rich in zeolite Y and which shows the absence of other impurities. This compared with preparation of zeolite Y seeding and without seeding methods using commercial silica which yields a mixture of zeolite Y and P.